2006
DOI: 10.1359/jbmr.060305
|View full text |Cite
|
Sign up to set email alerts
|

Association of Geometric Factors and Failure Load Level With the Distribution of Cervical vs. Trochanteric Hip Fractures

Abstract: We experimentally studied the distribution of hip fracture types at different structural mechanical strength. Femoral neck fractures were dominant at the lowest structural strength levels, whereas trochanteric fractures were more common at high failure loads. The best predictor of fracture type across all failure loads and in both sexes was the neck-shaft angle.Introduction: Bone geometry has been shown to be a potential risk factor for osteoporotic fractures. Risk factors have been shown to differ between cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
77
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 37 publications
15
77
0
Order By: Relevance
“…This follows the biomechanical concept that the wider the femoral NSA the higher the bending moment at the FN and the higher the impact force imposed on the FN, which results in a greater probability of fracture. 19,21,27,28 Therefore, the ability of NSA to predict hip fracture in males independent of BMD was examined. It was found not only that FN-BMD was the best hip fracture predictor in males but also that NSA does not predict hip fracture independent of FN-BMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This follows the biomechanical concept that the wider the femoral NSA the higher the bending moment at the FN and the higher the impact force imposed on the FN, which results in a greater probability of fracture. 19,21,27,28 Therefore, the ability of NSA to predict hip fracture in males independent of BMD was examined. It was found not only that FN-BMD was the best hip fracture predictor in males but also that NSA does not predict hip fracture independent of FN-BMD.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 This evidence, however, mainly derives from studies carried out in females, 9-13 whereas contradictory results characterize studies carried out in males. [14][15][16][17][18][19][20] Authors' opinions seem to vary widely about the ability of the neck shaft angle (NSA), one of the PFG factors, to predict osteoporotic hip fractures in males, [14][15][16]21 whereas its association with the risk of hip fracture in females 10,11,14,22 is generally accepted. Gender differences in the hip anatomy 23 have been put forward as a possible explanation for the different relationship of NSA with the hip-fracture risk between genders, whereas geographic and racial differences 24 among the examined male populations have been advocated as a possible cause of authors' discrepancies on the relationship between NSA and the hip-fracture risk in males.…”
Section: Advances In Knowledgementioning
confidence: 99%
“…(49) Trochanteric fractures also have been shown to be associated with increased mortality when compared with cervical fractures, and this could not be explained by differences in age or comorbidity. (4) Since there is evidence in both in vitro (14,15,42,47,50) and in vivo (3,30) studies that cervical and trochanteric fractures have different risk factors, we compared densitometric and geometric variables between the two subgroups and analyzed hip fracture discrimination separately for each subgroup. Compared with cervical fracture cases, we found lower DXA aBMD and QCT BMD values in trochanteric fracture cases, but differences were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with current knowledge that women with trochanteric fractures have a more severe and generalized low bone density involving particularly the trabecular component, with lower aBMD in the trochanteric region and lumbar spine. (51) Cervical fractures seem to depend more on proximal femur or pelvic geometry (such as a larger femoral neck shaft angle or a longer hip axis length in cervical fractures (2,3,30,50) ) combined with focal bone loss. (51) In the EPIDOS study, aBMD values of novel upper and lower femoral neck subregions were lower in trochanteric fractures than in controls, but prediction of cervical fractures was improved by measuring aBMD only in the upper subregion of the femoral neck.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the structural and material properties of the proximal femur determine the type of hip fracture. 1,2 Patients with trochanteric hip fractures have been found to have lower serum vitamin D levels compared to patients with femoral neck fractures. 3 Apart from studies done involving Caucasians, there is a paucity of information on other populations about the relationship of vitamin D levels and hip fracture subtypes; the interplay between 25(OH)D, intact PTH (iPTH), calcium and phosphorus; the impact of renal insufficiency; and the effect of premorbid ambulatory status on hip fracture type.…”
Section: Introductionmentioning
confidence: 99%